LCA analysis of a roof mounted PV system: a Romanian case study - Rus, Tania; Moldovan, Raluca-Paula; Pardo Picazo, Miguel Ángel (Frontiers in Environmental Science, 2024)
Using solar photovoltaic power sources has become a discussed topic in the construction and energy industry. The pressing need to reduce reliance on fossil fuels, increasing costs of traditional electricity generation, and affording photovoltaic modules has sparked a growing interest in solar photovoltaics. This study surveys the environmental impact of installing a solar panel system on a buildingaims to optimisze the layout of solar photovoltaic systems to minimizeminimise environmental impact and building load, comparing the performing south-oriented panels with east-west-oriented panels. The comprehensive analysis performed hinges on a diverse array of determinative factors that demand thoughtful consideration before embarking upon implementing any photovoltaic installation. These salient factors, including but not limited to structural integrity, incorporating ballast for stability enhancement, integrating requisite electrical components, selecting solar panels, quantifying energy production capabilities, assessing carbon emissions, and discerning associated benefits, require thoughtful consideration before implementing any photovoltaic installation. The findings derived from this study underscore that, within the context of the given geographical location, the solar photovoltaic system configured with an East-West orientation represents the optimal choice to reduce both emissions and structural load. This study provides a scientific basis for the construction industry and the energy field and guides the future development of photovoltaic installation projects in a more economic and environmentally friendly direction.